MANAJEMEN PEMBELAJARAN INTEGRATIF DALAM MATA PELAJARAN IPS DAN PAI DI MAS PONDOK PESANTREN DARUSSALAM KUNIR - Farihin, Ahmad; Tamam, Badrud; Agustian Widia Yusuf, Ilham; Tiara Aqila, Salma; Nabila, Syafiatun (Edum Journal, 2022)
This study aims to describe and analyze 1) The integrative learning process in social studies and PAI class X (ten) social studies. 2) What are the inhibiting factors in the integrative learning process in social studies and PAI subjects for class X (ten) IPS. 3) Supporting factors in the integrative learning process in social studies and PAI subjects for class X (ten) IPS in MA. PP. Darussalam Kunir. The method used in this research is the descriptive analysis method with a qualitative approach. Data collection techniques in this study were carried out alone, namely by conducting observations, in-depth interviews, and documentation. The subjects of this research are; principals, teachers, students, education staff, and parents. Data analysis was carried out by clarifying the data obtained and then collected for analysis and conclusions drawn. The mindset used is inductive. Based on the results of data analysis, it can be interpreted that: 1) The integrative learning process in social studies and Islamic studies subjects is to merge the separation between religion and social sciences, it is necessary to connect the social studies material with PAI or with the model injected general scientific theories related as the form of interconnectivity between the two, besides that, religious values ​​education is also given. 2) Obstacles in the integrative learning process in social studies and Islamic studies subjects are the lack of support for social science teachers' knowledge of the relationship with religion, minimal integration guidebooks, and the dichotomy between disciplines. 3) Supporting factors in the integrative learning process in IPS and PAI subjects are adequate facilities and infrastructure as well as support from the Head of Madrasah and the teacher of the subject concerned. From the results of the study, it can be concluded that integrative learning in social studies and PAI (Islamic Religious Education) subjects are very necessary because it can realize the ideals of education to form people who are knowledgeable, religious, and have good morals and can become complete human beings.